Intensity Corelation of Advertising Exposure, Intensity of Exhibition Exposure, and Communication Competency Level of Sales Person with Desire of Purchasing House at Grha Candi Golf Semarang - Fatia Sharfina; Djoko Setyabudi, S.Sos, MM (Interaksi Online, 2016)
Exposure to advertising not only serves as a notification or information to the consumer about a product, but also to influence someone to take a decision of buying products which have been promoted. Exposure is also not just about whether someone physically close enough to the presence of the mass media, but whether a person is truly open to the knowledge of the messages of the mass media. Exhibition is an activity that aims to demonstrate or promoting a product to consumers as a marketing target. Communication competence is the ability to communicate effectively. Competencies include such things as knowledge of the role of the environment (context) in influencing the content (content) and a form of communication messages. Advertising exposure, exposure intensity Competency Level Communications Exhibition and Sales Person potentially have relationships with buying interest a house at Graha Candi Golf Semarang. This study aims to determine the relationship of advertising Exposure, Intensity Exposure Level of Competence Communications Exhibition and Sales Person buying interest a house at Graha Candi Golf Semarang. The cornerstone of this research using the theory Advertising Exposure Process Activation Theory of Information Exposure, Specch Act and Theory of Reasoned Action (TRA). This type of research tends explanatory study with the technique of sampling in this research was done by using a non-probability sampling type of convenience sampling. Total sample of 30 respondents with criteria that respondents were searching a house in Semarang, Exposed Ad Exposure, Exhibition Exposed and having experience Communicate with Sales Person Graha Candi Golf. Testing the hypothesis in this study using a test Kendall’s Tau_b with the help of SPSS applications. Based on the results of testing the hypothesis by using statistical test of Kendall's Tau_b showed that there is no significant correlation between the intensity of advertising exposure relationship Grha Temple Golf (X1) with buying interest a house at Graha Candi Golf Semarang (Y). It can also prove that these two variables have no correlation. The second hypothesis test using Kendall's Tau_b statistical test showed that there is no significant correlation between exposure intensity relationships exhibition Grha Temple Golf (X2) with buying interest a house at Graha Candi Golf Semarang (Y). It can also prove that these two variables have no correlation. The third hypothesis testing using Kendall's Tau_b statistical test showed that there is a significant correlation between the level of communication competence of sales person Graha Candi Golf (X3) with buying interest a house at Graha Candi Golf Semarang (Y). It can also prove that these two variables have a correlation, the higher the level of communication competence possessed Graha Candi Golf sales person, the higher the interest of potential customers to own a house at Graha Candi Golf Semarang.